2009
DOI: 10.1261/rna.1618809
|View full text |Cite
|
Sign up to set email alerts
|

The aminoglycoside resistance methyltransferase Sgm impedes RsmF methylation at an adjacent rRNA nucleotide in the ribosomal A site

Abstract: Ribosome-targeting antibiotics block protein synthesis by binding at functionally important regions of the bacterial rRNA. Resistance is often conferred by addition of a methyl group at the antibiotic binding site within an rRNA region that is already highly modified with several nucleotide methylations. In bacterial rRNA, each methylation requires its own specific methyltransferase enzyme, and this raises the question as to how an extra methyltransferase conferring antibiotic resistance can be accommodated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…3D), peaks at m/z 1305 and 3181 were missing and replaced by a longer fragment at m/z 4469 corresponding to the C1402-G1415 sequence but with only two methyl groups. The m 7 G1405 modification must be present in the peak at m/z 4469 to prevent its cleavage by RNase T1; taken together, these data indicate that it is one of the two rRNA methylations at C1402 that is missing rather than that at C1407 as previously suggested (Cubrilo et al 2009;Gutierrez et al 2012). …”
supporting
confidence: 65%
See 3 more Smart Citations
“…3D), peaks at m/z 1305 and 3181 were missing and replaced by a longer fragment at m/z 4469 corresponding to the C1402-G1415 sequence but with only two methyl groups. The m 7 G1405 modification must be present in the peak at m/z 4469 to prevent its cleavage by RNase T1; taken together, these data indicate that it is one of the two rRNA methylations at C1402 that is missing rather than that at C1407 as previously suggested (Cubrilo et al 2009;Gutierrez et al 2012). …”
supporting
confidence: 65%
“…3B). The presence of the C1402-G1415 fragments resistant to cleavage by RNase T1 indicated that ArmA methylation is complete but that one of these endogenous modifications is no longer stoichiometric, as already shown for other G1405 methyltransferases (Cubrilo et al 2009;Gutierrez et al 2012). To discriminate between partial interference at position C1402 or C1407, pIP1204 was introduced into MM294ΔrsmF.…”
Section: Plasmid Pip1204-mediated Arma Has An Impact On the Hostmentioning
confidence: 72%
See 2 more Smart Citations
“…It is interesting, however, that compounds 5, 7 and 15 showed less evident antibacterial activity, either on the strain resistant to macrolide antibiotics or on the sensitive DH5a strain, while 10, 16 and 17 showed stronger antibacterial activity on the strain resistant to aminoglycoside antibiotics. Aminoglycoside resistant strain expressed 16S rRNA methyltransferase Sgm, a member of the Arm family of enzymes that methylate the N 7 position of residue G1405 within the decoding-or A-site in the small ribosomal subunit (23). This modification prevents 4,6-disubstituted 2-deoxystreptamine aminoglycosides from binding to the A-site, thus rendering them bacteria resistant (12).…”
Section: Antibacterial Activitymentioning
confidence: 99%